The Rise in Education Attainment in MENA in Comparative Perspective - Iqbal, Farrukh (World Bank, Washington, DC, 2015)
While education stocks (measured as the number of years of schooling attained per person over age 15) have risen significantly in all regions, they have risen the fastest in the Middle East and North Africa (MENA) region. This note documents this remarkable regional achievement. This brief shows that all 15 MENA countries for which we have comparable data increased their education stocks over time. As well as trends in population weighted averages for education stock across regions.